Narrating Curriculum Transformation in Islamic Boarding School: Integrating Tradition and Digital Practices in Islamic Boarding School Education - Salis Irvan Fuadi; Raharjo Raharjo; Ikhrom Ikhrom; Laila Ngindana Zulfa (Yayasan Adra Karima Hubbi, 2026)
Background: Digital technology is an important part of Islamic boarding schools that need to pay attention to Islamic educational institutions in the archipelago. The rapid development of digital technology urges Islamic educational institutions, including salaf Islamic boarding schools, to transform curriculum design to remain relevant while preserving traditional identity. Integrating classical Islamic values with technological innovation presents both challenges and opportunities in pesantren education. Purpose: This study aims to analyze the curriculum design of Al-Asy’ariyyah Islamic Boarding School, Kalibeber Wonosobo, in adapting to technological developments in the digital era. Method: A mixed-methods approach was employed using questionnaires, interviews, observations, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were processed through data reduction, presentation, and conclusion drawing. Results: The findings indicate that the curriculum maintains traditional sorogan and bandongan learning methods while integrating digital technology utilization. Approximately 50% of respondents produced fiqh content, 23% moral content, 17% hadith content, and 10% interpretative content. The dominant media included images (63%), videos (26%), and animations (11%), while digital tools facilitated learning interaction and online academic communication. Conclusion: The pesantren curriculum demonstrates adaptive, flexible, and collaborative characteristics through integrating traditional Islamic education with digital technology while sustaining Islamic and local cultural values.